Efficacy and safety of an herbal galactagogue decoction versus powdered formulation in lactating rats - Pruksa Chotitham; Suksalin Booranasubkajorn; Saracha Pattanapholkornsakul; Pravit Akarasereenont; Pinpat Tripatara (Phytomedicine Plus)
Background: An herbal galactagogue formula in Thai traditional medicine, known as the Prasanamnom formula (PNF), has been utilized to increase maternal breast milk. The traditional method of administering PNF is via decoction, which has become inconvenient in modern times. Consequently, it has been newly produced in a powdered form for capsule prescription. However, the efficacy and safety of PNF in either form have not been studied. Purpose: This study investigated the effects of PNF decoction and powder on milk production and their safety regarding organ functions. Methods: Maternal rats were administered distilled water, PNF decoction (300, 600, 1000 mg/kg), or PNF powder from the capsule (100, 300, 1000 mg/kg), or given 10 mg/kg domperidone as a positive control, once daily on postnatal days (PND) 1 to 21. Milk yield was estimated by pup weight. Analyses were conducted on maternal blood samples collected on prenatal days, and PND 7, 14, and 21, and pup blood samples collected on PND 22. Results: PNF decoction (600 mg/kg) and domperidone significantly increased the mean of milk production and serum prolactin level when compared with the vehicle control. The PNF powder had no such effects. Both PNF decoction and powder did not exhibit subacute toxicity to the liver and kidneys in maternal rats and pups. Conclusion: The effectiveness of the PNF decoction in improving both milk production and prolactin levels was similar to that of domperidone. Additionally, the traditional decoction method was effective in increasing milk production and elevating serum prolactin levels in mother rats.